A livability evaluation framework using a multi-source data and network science approach – applied to the cities of Bacoor and Makati, Philippines - Ong, Deanne Jaimelyn Ang (Animo Repository, 2022)
Evaluating livability is vital to understanding a city’s living conditions. It serves as a guiding principle in policy-making and sustainable urban planning, catering to the people’s basic and psychological needs. Over the years, Metropolitan Manila, Philippines, has been plagued by overpopulation and congestion. To counter this, the national government has aimed to shift urban development to cities outside the capital region. This imposed a need for a people-centered and sustainable livability evaluation framework to determine the areas for improvement in these cities to attract people. This study aimed to establish and apply a new data-driven framework for evaluating livability – utilizing the normative and objective approaches to Bacoor City and Makati City, Philippines. A combination of quantitative and geospatial data was applied to a livability model appropriated to secondary cities in the ASEAN. Network analysis was also done to investigate the accessibility of common and critical facilities for walking, biking, and driving commutes. Community detection was used to identify clusters of accessible facilities and their diversity. A linear programming model that aimed to maximize the livability model with some defined constraints was generated and tested, given a percentage increase in the livability indicator scores. Bacoor obtained a moderate livability score, whereas Makati obtained a satisfactory livability score. The existing road network and lesser facilities in Bacoor contributed to a poorer performance than that of Makati. The commercial zones of both cities dominated the livability scores as most facilities were situated in these areas. Regarding accessibility, most types of facilities were primarily accessible by car in Bacoor, while a diverse variety of facilities were already accessible by bicycle in Makati. Although, there was a disproportionate distribution and diversity of facilities within communities of both cities. Overall, this framework and its results can assist local government units in making their cities more livable.